Nilai-Nilai Pendidikan Islam Dalam Tradisi Berpantang 40 Hari Setelah Melahirkan Pada Masyarakat Melayu Sambas - Sriliza Sriliza (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This research was carried out in Temajuk Village, Paloh District, Sambas Regency which raised the values of Islamic education in the tradition of abstinence 40 days after giving birth to the Sambas Malay community in Temajuk Village, Paloh District, Sambas Regency. the approach in this research is qualitative. The type of research used in this research is a case study. The results of this study are as follows: 1) the values of creed education in the tradition of abstinence 40 days after giving birth to the Sambas Malay community in Temajuk Village, Paloh District, including a) a strong belief in obeying the applicable rules in abstinence for 40 days which is in line with the postpartum which is taught in Islam, b) belief in husband, parents, family and others in the implementation of abstinence 40 days after giving birth. 2) the values of worship education in the tradition of abstinence 40 days after giving birth to the Sambas Malay community in Temajuk Village, Paloh District, including a) obeying traditional teachings and rules that are in line with Islamic teachings and rules, such as not praying during the puerperium and unrelated husband and wife, b) get used to pray, glorify God and read religious books. 3) the values of moral education in the tradition of abstinence 40 days after giving birth to the Sambas Malay community in Temajuk Village, Paloh District, including a) obeying and following the rules of abstinence that have been passed down from generation to generation, b) obeying orders, teachings, and advice from parents, c) do good and be polite to family and others.